New paradigms in running injury prevention - Benno M. Nigg on target - Markus Tilp (Ed.) (Bern Open Publishing, 2018)
In this target article (TA; CISS_2017_007), Benno M. Nigg, Maurice M. Mohr, and Sandro R. Nigg explain and criticize the two main paradigms ('impact' and 'pronation') in running injury prevention research of the last 40 years and present new paradigms on 'muscle tuning', 'preferred movement path', and 'functional groups'. The main article (CISS2017_007) is then discussed by six peer commentaries (CISS2018_102 - CISS2018_107), authored by sport scientists that are experts in the field. Finally, critiques, suggestions, and extensions brought forward by the commentators are acknowledged by Nigg and co-authors in their closing response (CISS2019_001).